Anti-inflammatory activity of centella asiatica - Isuparan, Dinishkumari (Universiti Sains Malaysia, 2012)
Centella asiatica (C.asiatica) is a member of a tropical plant family, traditionally used as anti-inflammation and for wound healing. Macrophage plays a primary role in innate macrophage cells stimulated with the plant extracts was initially investigated by MTT cell proliferation assay and the anti-inflammatory activity of C.asiatica was determined by measuring its effect on the H2O2 and NO production by the stimulated macrophage cells. The data were analyzed using ANOVA and Tukey’s post hoc test. The result showed that the methanolic leaves extract of the plant enhances the highest proliferation of the J774A. 1 macrophage cell at 150 pg/mL. It was also found that the extract has a significant anti-inflammatory effect in terms of cell proliferation, suppressing NO and H2O2 production in concentration-dependent manner as compared to the control groups.